SAT0090 Evaluation of the use of ultrasound to manage patients with rheumatoid arthritis over time: results from the corrona registry. (12th June 2018) - Pappas, D.A.; Saunders, K.C.; Etzel, C.J.; Hua, D.W.; Deering, K.; Zueger, P.; Garg, V.
Abstract : Background: Musculoskeletal ultrasound (MSUS) imaging in patients with rheumatoid arthritis (RA) can detect synovial inflammation with higher sensitivity compared to physical examination alone. 1 Not all rheumatologists have adopted the use of MSUS in their daily practice. Objectives: To compare clinical outcomes in patients whose physicians use MSUS to assess joint inflammation vs those who do not. Methods: Data from patients≥18 years old with a confirmed diagnosis of RA who had an index visit in the Corrona RA Registry from 01/01/2012 to 12/31/2015 with ≥12 months of follow-up were stratified into 2 groups: patients whose physicians use MSUS frequently—ie, in >50% of their patient encounters—(MSUS group) and patients whose physicians do not use MSUS at all (No-MSUS group). Frequency of MSUS can be recorded and updated by the rheumatologist in the registry questionnaires at every Corrona visit. The index visit was the first visit in which the physician reported the frequency of MSUS use. Outcomes included mean Clinical Disease Activity Index (CDAI) and the proportion of patients in low disease activity (LDA)/remission (CDAI ≤10) at each time point and were evaluated at index and 1, 2, and 3 years post-index. Comparisons between groups were made using 2-sample t -tests for mean CDAI and Chi-square tests for achievement of LDA/remission. Results: 21 physicians reported using MSUS frequently compared with 111 who did not use MSUS at all. 5446 of their patients met the criteria for analysis; 1018 (18.7%) were in the MSUS group and 4428 (81.3%) were in the No-MSUS group. At the index visit, the MSUS group was younger (mean age 57.7 years vs 59.8 years, p<0.01) and had shorter disease duration (mean 8.7 years vs 11.0 years, p<0.01) compared with the No-MSUS group. At the index visit, the MSUS group had lower mean CDAI (9.7 vs 12.6, p<0.01) and a greater proportion of patients in LDA/remission (64.9% vs 56.8%, p<0.01) compared with the No-MSUS group; these differences were also present at 1, 2, and 3 years post-index (figure 1). Conclusions: A greater percentage of patients whose physicians use MSUS were in LDA/remission over time. Average disease activity of these patients was lower compared with patients whose physicians did not use MSUS. This pattern was observed at 4 different time points over a 3 year period. Reference: [1] Freeston, et al. Ann Rheum Dis2010;69:417–9. Acknowledgements: Corrona has been supported through contracted subscriptions in the last 2 years by AbbVie, Amgen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Crescendo, Eli Lilly and Company, Genentech, Gilead, GSK, Horizon Pharma USA, Janssen, Merck, Momenta Pharmaceuticals, Novartis, Pfizer Inc, Roche, UCB and Valeant. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Medical writing services provided by Joann Hettasch of Fishawack Communications and funded by AbbVie. Disclosure of Interest: D. Pappas Shareholder of: Corrona, Employee of: Corrona, Paid instructor for: Novartis, K. Saunders Shareholder of: Corrona, Employee of: Corrona, C. Etzel Shareholder of: Corrona, Employee of: Corrona, D. Hua: None declared, K. Deering Employee of: EPI-Q, P. Zueger Shareholder of: AbbVie, Employee of: AbbVie, V. Garg Shareholder of: AbbVie, Employee of: AbbVie